Analysis of Vsat Gyro performance based on the power level of the antenna receiver on the Pelni ship - imelda uli vistalina simanjuntak; Sulistyaningsih Sulistyaningsih; Ketty Siti Salamah; Krisna Yudha Dewantara (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The satellite communication system that is used for ship communication in Indonesian waters is expected to transmit real time data at any time under any conditions. However, currently, the Vsat Gyrsoscope antenna that is installed on the Pelni ship still uses the Ku band frequency. This frequency band is very susceptible to rain attenuation. Vsat Gyro will automatically search for satellites that cover it. Only when it is raining and the ship is moving towards the port, is there a decrease in the receiving power level. SNR and power and C/N will drop. Therefore, it is necessary to do an analysis to overcome this problem so that it is not disconnected during the transmission. This study conducted an analytical study to validate the analytical predictions of phasing the vsat power signal level on the pelni ship to maintain communication during sea operations, which are included in TKT 3 (three). The tools used in the measurement are vsat modem, PRTG application, laptop, RJ 45 cable, and Spectrum Analyzer. By optimizing the calculation of the margin link budget, the calculation of Qos and the parameters vsat Eb/No, C/N and SNR when adjusted to the operating conditions of the ship with high rain intensity so that communication can continue to run even when the worst conditions can be maintained properly.Â